2006
DOI: 10.1097/01.psy.0000238216.88515.e5
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Stress Reactivity in Metastatic Breast Cancer

Abstract: Depression in patients with MBC was associated with alterations in autonomic regulation, particularly reductions in respiratory sinus arrhythmia, a measure of cardiac vagal control, at baseline and during the TSST. In addition, depression was associated with blunted HPA response to awakening. Both MBC groups had relative cortisol hyporesponsiveness to acute stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 57 publications
1
76
2
Order By: Relevance
“…One large and heterogeneous diagnostic category, depression, has produced conflicting results with regard to the CAR: some studies described a blunted CAR in patients with depression (Stetler and Miller, 2005;Huber et al, 2006), in metastatic breast cancer patients with depression (Giese- Davis et al, 2006) or in subjects with cognitive vulnerability markers of depression (self-focused rumination, Kuehner et al, 2007), and others reported an increased CAR in depressed patients (Bhagwagar et al, 2005) or individuals with self-reported depressive symptoms (Pruessner et al, 2003). As depression is a very heterogeneous diagnostic group, it seems very likely that different subtypes (e. g. atypical vs. melancholic depression) have to be considered separately to obtain consistent results (see also Gold and Chrousos, 2002).…”
Section: Factors That Influence the Carmentioning
confidence: 98%
“…One large and heterogeneous diagnostic category, depression, has produced conflicting results with regard to the CAR: some studies described a blunted CAR in patients with depression (Stetler and Miller, 2005;Huber et al, 2006), in metastatic breast cancer patients with depression (Giese- Davis et al, 2006) or in subjects with cognitive vulnerability markers of depression (self-focused rumination, Kuehner et al, 2007), and others reported an increased CAR in depressed patients (Bhagwagar et al, 2005) or individuals with self-reported depressive symptoms (Pruessner et al, 2003). As depression is a very heterogeneous diagnostic group, it seems very likely that different subtypes (e. g. atypical vs. melancholic depression) have to be considered separately to obtain consistent results (see also Gold and Chrousos, 2002).…”
Section: Factors That Influence the Carmentioning
confidence: 98%
“…For each 5-min segment, five 1-min averages of HR extracted by the VivoLogic software were averaged. For the HRV measures, the ECG and respiration signals for each of the 5-min segments were imported into customized programs (for details, see Giese-Davis et al, 2006) and edited for artifacts. The variance in the RR-interval signal was decomposed via spectral analysis to yield a set of frequency domain indices representing the spectral power within distinct frequency bands [HF (0.13 -0.5 Hz), LF (0.04 -0.13 Hz), and VLF (0.003 -0.04 Hz)].…”
Section: Physiological Measuresmentioning
confidence: 99%
“…Flatter daytime slopes of cortisol have been associated with fatigue in breast cancer patients [14,15] and were predictive of earlier mortality with metastatic breast cancer [16], independent of other known prognostic factors. In addition, depression was associated to blunted stress reactivity in metastatic breast cancer [17]. Recent work suggested that flatter daytime cortisol slopes among metastatic breast cancer patients may be related to disrupted feedback inhibition of the HPA axis rather than hypersensitivity in response to stimulation [18].…”
Section: Introductionmentioning
confidence: 98%